Trends in Sport Sciences: formerly Studies in Physical Culture and Tourism 2013 Vol.20 No.2 - Urbański, Piotr; Bauerfeind, Joanna; Pokaczajło, Jarosław (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Carrying out the investigation of community integration (CI) seems to be important part of research in rehabilitation in persons with spinal cord injury (SCI).Researchers point out the need for continuing study of the factors which may modifie level of CI in this group. Aim of Study. The main purpose of this study was to assess the CI level in SCI athletes, participating in individual sports (IS), and team sports(TS). The additional purpose was to identify other variables that determine the level of CI. Material and Methods. The study participants (n = 30) were divided due to practiced sport, into two groups: IS (n = 15), and TS (n = 15). Athletes completed measures of CI: Community Integration Questionnaire (CIQ),and demographic questionnaire (containing information about such variables, as: age in the day of study, time elapsed from injury, level of injury, and level of physical activity – measured by number of hours spent for training per week). Results. There were no significant difference between level of CI in SCI athletes participating in IS, and TS. There were significant difference between physical activity level (measured by number of hours spend for training per week) and one of three subscales, that contains to CIQ. Conclusions. The study results confirmed the need to increase level of physical activity in persons with SCI, and extend research about determinants of CI.
Keywords: spinal cord injuries; community integration; team sports; individual sports; physical activity